A comprehensive evaluation of the left atrium using cardiovascular magnetic resonance - Maurice Pradella; Mohammed S.M. Elbaz; Daniel C. Lee; KyungPyo Hong; Rod S. Passman; Eugene Kholmovski; Dana C. Peters; Justin J. Baraboo; Daniel A. Herzka; Reza Nezafat; Robert R. Edelman; Daniel Kim (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Atrial disease or myopathy is a growing concept in cardiovascular medicine, particularly in the context of atrial fibrillation, as well as amyloidosis and heart failure. Among cardiac imaging modalities, cardiovascular magnetic resonance (CMR) is particularly well suited for a comprehensive assessment of atrial myopathy, including tissue characterization and hemodynamics. The goal of this review article is to describe clinical applications and make recommendations on pulse sequences as well as imaging parameters to assess the left atrium and left atrial appendage. Furthermore, we aimed to create an overview of current and promising future emerging applications of left atrium-specific CMR pulse sequences focusing on both electrophysiologic (EP) and non-EP applications.